State and intellectuals in Turkey the life and times of Niyazi Berkes, 1908--1988 - Dinçşahin, Şakir (Lexington Books, 2015)
"Niyazi Berkes was among the most prominent figures in Turkish political thought in the Republican period. He was the author of several masterpieces that broke new ground in the fields of Turkish politics and history. Berkes not only witnessed political history but was also influential in shaping Turkish identity. In fact, the Young Turk Revolution (1908), the War of Independence (1919-1922), the reforms of Kemal Atatürk (1923-1938), the construction of a Kemalist ideology and its transformation during World War II (1939-1944), and the Cold War (1945-1989) are some of the weighty matters of Turkish history that were part of his life story. Berkes's political and intellectual biography thus affords a unique vantage point from which to study both Turkish political thought and the interplay between political history and an intellectual biography. This book also sheds light on recent political developments in contemporary Turkey, suggesting that the challenges to inculcate the democratic vision that originated in Berkes's lifetime continue today." -- Back cover.